Avaliação da expressão imuno-histoquímica de marcadores de hipóxia em carcinoma epidermóide de língua - Vasconcelos, Marcelo Gadelha (2014)
The tumor hypoxia modulates a series of genetic changes related to adaptive development, invasion and metastasis of various human cancers, among which squamous cell carcinoma of the tongue (SCCT). The objective of this study was to analyze clinical, morphological and immunohistochemical expression by HIF-1α, GLUT-1 and CA-IX in 57 cases of CEL and correlated this expression to clinical parameters and morphological. After a descriptive analysis of data on gender, age, race, and habits of patients, it was found that the results were consistent with the literature. The clinical and morphological parameters analyzed and the expression of these markers of hypoxia were subjected to statistical analysis (Qui2 test), verifying that they can be used as indicators of the biological behavior of CEL. Among the results of this study, we observed that the intensity of expression for HIF-1α, in most cases located in the cytoplasm and nucleus, statistically correlated with clinical staging (p = 0.011) and histological grading (p = 0.002). As for the relationship between the distribution of labeling for HIF-1α and metastasis, the chi-square (Qui2) showed that there was statistically significant differences between the groups (p = 0.040). 75.8% of the sample who had metastases, there was the predominance of diffuse marking. The immunoexpression cytoplasmic/membrane GLUT-1 showed a statistically significant correlation with the clinical stage (p = 0.002) and histological grading (p = 0.000). Concerning the location of markings for GLUT-1 tumor on the island, there was a predominance of peripheral marking specimens in most low-grade (78.6%). In the sample of high-grade, prevailed the location center/periphery (55.8%). According to the chi-square (Qui2), the location on the island of the tumor (p = 0.025) showed statistically significant difference in histological grading. The immunoreactivity of CA-IX, in most cases located in the membrane and cytoplasm, exhibited a statistically significant correlation with histological grading (p = 0.005). Based on these results, we can conclude a broad participation of these markers of hypoxia in oral carcinogenesis and its possible use as markers of biological behavior and tumor progression in CEL